Question
upstudy study bank question image url

\( 2.2 \quad \) Given: \( \sum_{p=k}^{10} 3^{p-1}=29520 \). Calculate the value of \( k \).

Ask by Crawford Welch. in South Africa
Feb 19,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The value of \( k \) is 3.

Solution

We are given the equation   ∑ from p = k to 10 of 3^(p – 1) = 29520. Step 1. Rewrite the sum in a more convenient form. Let i = p – 1, so when p = k, i = k – 1, and when p = 10, i = 9. Then the sum becomes   ∑ from i = k – 1 to 9 of 3^i. Step 2. Use the formula for the sum of a geometric series:   ∑ from i = m to n of r^i = (r^(n + 1) – r^m)/(r – 1). In our case, r = 3, m = k – 1, and n = 9. So   ∑ from i = k – 1 to 9 of 3^i = (3^(10) – 3^(k – 1))/(3 – 1) = (3^(10) – 3^(k – 1))/2. Step 3. Set the sum equal to 29520 and solve:   (3^(10) – 3^(k – 1))/2 = 29520. Multiply both sides by 2:   3^(10) – 3^(k – 1) = 59040. Step 4. Calculate 3^(10):   3^(10) = 59049. Substitute into the equation:   59049 – 3^(k – 1) = 59040. Subtract 59040 from 59049:   3^(k – 1) = 59049 – 59040 = 9. Since 9 = 3^2, we have:   3^(k – 1) = 3^2. Thus, equate the exponents:   k – 1 = 2  →  k = 3. The value of k is 3.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To solve the equation \( \sum_{p=k}^{10} 3^{p-1} = 29520 \), we first rewrite the summation: \[ \sum_{p=k}^{10} 3^{p-1} = 3^{k-1} + 3^k + 3^{k+1} + \ldots + 3^{9} + 3^{10} \] This can be recognized as a geometric series. The first term of the series is \( 3^{k-1} \) and the last term is \( 3^{9} \). The number of terms in this series is \( 10 - k + 1 = 11 - k \). The sum of a geometric series can be calculated using the formula: \[ S_n = a \frac{r^n - 1}{r - 1} \] where \( a \) is the first term, \( r \) is the common ratio, and \( n \) is the number of terms. Here, \( a = 3^{k-1} \), \( r = 3 \), and \( n = 11 - k \). Thus, the sum becomes: \[ \sum_{p=k}^{10} 3^{p-1} = 3^{k-1} \frac{3^{11 - k} - 1}{3 - 1} = 3^{k-1} \frac{3^{11 - k} - 1}{2} \] Setting this equal to \( 29520 \): \[ 3^{k-1} \frac{3^{11 - k} - 1}{2} = 29520 \] Multiplying both sides by 2 gives: \[ 3^{k-1} (3^{11 - k} - 1) = 59040 \] Now, we can simplify \( 3^{k-1} (3^{11 - k} - 1) \): \[ 3^{k-1} (3^{11 - k} - 1) = 3^{10} - 3^{k-1} = 59040 \] Calculating \( 3^{10} \): \[ 3^{10} = 59049 \] Therefore, we can now rewrite the equation: \[ 59049 - 3^{k-1} = 59040 \] This leads us to: \[ 3^{k-1} = 59049 - 59040 = 9 \] Since \( 9 = 3^2 \): \[ k - 1 = 2 \quad \Rightarrow \quad k = 3 \] Thus, the value of \( k \) is \( \boxed{3} \).

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy